Intervenção pedagógica individualizada para alunos com deficiência intelectual : ensino de leitura em salas de recursos - Oliveira, Glaucimara Pires (Universidade Federal de São Carlos, 2010)
In contemporary society the acquaintance of reading is considered a fundamental resource for the individual s citizenship achievement. Despite the schools dedication to their students, there is no guarantee that all students learn with the mastery and fluency required. Within this context , there are students who present Intellectual disabilities , and by their specific characteristics have significant limitations, both in intellectual functioning and in adaptive behavior. Many of these students are inserted in regular schools which offer assistance in specialized pedagogical extra hours, but nevertheless they often reach the upper grades of elementary school without the necessary reading and comprehension skills . Studies in the area of stimulus equivalence have demonstrated that the application of systematic methodologies with individualized procedures can reverse that problem in several steps and ways of teaching. The purpose of this research study was to verify the effectiveness of an individualized reading e writing Program in order to improve the skills of students with intellectual disabilities , and attend the resource classes at elementary school. The participants were two students, which presented different stages of literacy, both students with intellectual disabilities enrolled in primary education in regular classes and resource rooms. The participant 1 was exposed to the program 1, which teaches the reading of simple words( consonant vowel ) and the participant 2 was exposed to the program 2, which teaches the reading of more complex language s words . In both cases the results indicated the effectiveness of the teaching reading Program. In conclusion It could be verified that the effectiveness of the Program as an additional instructional procedure to those already used in the classroom, since it enhances the student s learning in Literacy. The resource room features as a specialized pedagogical service with different resources and It can be effective, with small number of students, as an important space to the application of the program as well as monitoring the student s performance.
Keywords: Educação especial; Sala de recursos; Programa individualizado de leitura; Deficiência intelectual; Equivalência de estímulos; Special educacion; Resource classes; Individualized Reading Program; Intellectual disabilities; Stimulus equivalence; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL